Performance evaluation of hot-wall condenser in a domestic refrigerator - Peker, Gokmen; Ozkan, Derya Burcu (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In this study, the heat transfer performance of a hot-wall condenser, which is affected by design parameters, is investigated. In this study, the pipe section form (O/D) variation, which has not been examined so far, is used as a design parameter for condenser performance. Incorporating the specified design parameters, 12 different condenser samples were manufactured. Additionally, a simulation model regarding with the thermal effects was designed for comparing the outputs of experimental results. The parameters are outer diameter of the condenser pipe (4.0 and 4.76 mm), condenser pipe pitch (20, 40, and 60 mm), the section form (O/D) of condenser pipe, and the refrigerant mass flow rate in flow. The results revealed significant findings regarding the impact of different design parameters on the heat transfer rate of the condenser. Specifically, increasing the condenser pipe diameter led to an average heat transfer rate increase of 8.9% and 5.2% by increasing flow rates as double, respectively. The pipe pitch was found to have a notable effect on the heat transfer rates, resulting in average increases of 213%, 47%, and 313% for the 20-40 mm, 40-60 mm, and 20-60 mm transitions, respectively. Specifically, the novel output is the transition from O-to-D pipe configuration, resulting in a maximum 3% increase in the total heat transfer rate.
Keywords: Hot-wall condenser; Refrigerator; Heat transfer; Pipe form; Experimental tests; Heat transfer model; NATURAL-CONVECTION; Thermodynamics; Energy & Fuels; Engineering; Mechanics